Pattern of Child and Adolescent Patients Attending Psychiatric Outpatient Department of the Mental Hospital in Bangladesh (Faridpur Medical College Journal, 2013)
Bangladesh has only one mental hospital which is situated in Pabna district of the country. People from the nearby locality as well as from distant regions of the country come here for psychiatric service. Clinical records of all the children who attended the outpatient department of 'Mental Hospital, Pabna' (MHP) during January, 2009 to June, 2009 were analyzed. Of the 143 children, 125 (88%) were of school going age (i.e., ?6 years of age). The majority (63%) of the patients were male. International Classification of Diseases (ICD) classification revealed that the patients came with mental retardation (F70-F79) (38%), Episodic and paroxysmal disorder (G43-G44) (26%) and Schizophrenia, schizotypal & delusional disorders (F20-F29) (22%). The main comorbid condition was behavioural problem with mental retardation (43% of mentally retarded). Of the 103 patient we had information about the   pathway to care, 20 patients (19%) came directly to MHP and the rest 83 (81%) consulted other service provider before reaching here. Among the previous service providers, there were medical graduates (60%), Kobiraj (36%) and indigenous & religious healer (34%). Considering the variety of presentation of child and adolescent patients, we   propose to establish a multidisciplinary approach in MHP. DOI: http://dx.doi.org/10.3329/fmcj.v7i2.13501 Faridpur Med. Coll. J. 2012;7(2):67-70